2021
DOI: 10.1002/er.7467
|View full text |Cite
|
Sign up to set email alerts
|

Arginine‐glycine‐aspartate ( RGD ) peptide‐modified graphene as efficient support material for Pt electrocatalyst in proton exchange membrane fuel cells

Abstract: Graphene with its two-dimensional structure and unique properties has immense potential in energy-related applications such as proton exchange membrane (PEM) fuel cells. Herein, we employ a well-known biomolecule arginine-glycine-aspartate (RGD) peptide-functionalized graphene-supported Pt nanoparticles as an electrocatalyst for PEM fuel cells for the first time. First, chemically reactive graphene oxide (GO) is used as a precursor to covalently functionalize it with RGD peptide through amide bond formation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The bands at 2958 and 1200 cm −1 correspond to the stretching vibrations of alkane ( ν CH) and aliphatic amine ( ν C–N), respectively, in the backbone of the RGD peptide, whereas the band at 1133 cm −1 corresponds to the stretching vibrations of the epoxy group ( ν C–O). 27 Furthermore, the broad band near 3423 cm −1 and the weak band around 3219 cm −1 originate from ν OH and ν NH, respectively. The bands at 1427 and 1370 cm −1 are primarily due to δ CH, whereas the bands at 840, 800, and 723 cm −1 correspond to γCH.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The bands at 2958 and 1200 cm −1 correspond to the stretching vibrations of alkane ( ν CH) and aliphatic amine ( ν C–N), respectively, in the backbone of the RGD peptide, whereas the band at 1133 cm −1 corresponds to the stretching vibrations of the epoxy group ( ν C–O). 27 Furthermore, the broad band near 3423 cm −1 and the weak band around 3219 cm −1 originate from ν OH and ν NH, respectively. The bands at 1427 and 1370 cm −1 are primarily due to δ CH, whereas the bands at 840, 800, and 723 cm −1 correspond to γCH.…”
Section: Resultsmentioning
confidence: 96%
“…25 A short arginine–glycine–aspartic (RGD) amino acid sequence tripeptide, present in several extracellular matrix (ECM) proteins, serves as a primary recognition site for cell-membrane integrin receptors that mediate cell adhesion to the ECM, 26 which are used to stimulate cell adhesion and growth. 27 Experiments on HUVEC attachment in vitro demonstrated that RGD-grafted substrates significantly enhanced cell attachment. 28 Therefore, Fe–BTC/RGD/SPE was prepared via a combination of Fe–BTC having electrocatalytic performance toward NO with RGD promoting cell adhesion and growth and it was utilized for the rapid and sensitive detection of NO released from HUVECs.…”
Section: Introductionmentioning
confidence: 99%